The Influence of Service Quality and Customer Satisfaction on Customer Loyalty in The South African Retail Petroleum Industry - Khaliphayo, Musawenkosi (University of the Witwatersrand, Johannesburg, 2024)
The South African petroleum products industry is a significant contributor to the South African economy. Like every other industry, its business environment is dynamic and prone to rapidly changing circumstances, thus companies must reinvent their operations to successfully deliver superior customer value. In today's competitive environment, businesses compete strategically based on marketing strategies to influence consumers to gain a competitive advantage. Retail petrol stations do not compete based on price or product qualities because these factors are regulated by the government. The uniformity of product and price means that there are other factors, or not, that consumers use to base their choice of petrol or diesel filling station. The purpose of this study was to evaluate the influence of service quality and customer satisfaction on customer loyalty in the South African retail petroleum industry, using empirical studies based on primary survey data and verifiable hypotheses. This study undertook a quantitative approach in which a questionnaire was distributed to explore the influence of service quality dimensions on customer satisfaction, the influence of customer satisfaction on customer loyalty, and lastly, the influence of perceived service quality directly on customer loyalty. The findings of the study supported all three proposed hypotheses. The findings of this study contribute to knowledge by providing an empirical exploration of the determinants of consumer preference regarding petrol station service outlet selection. This study also adds to existing literature on how service quality dimensions can be used as a lever to maintain customers and inadvertently grow company profits in the South African retail petroleum industry context. The findings of this study provide marketing practitioners with an understanding of strategies that can be employed to influence consumers buying behaviour through the design of an industry specific SERVQUAL model. This study outlines the strategies, methods and suggests further research that can explored by future researchers. This study also adds value by showing how structural equation modelling can be used as a statistical tool to model consumer behaviour in different industries
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management,Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: South African retail petroleum industry; Service Quality; Customer Satisfaction; Loyalty; UCTD; SDG-8: Decent work and economic growth